2018
DOI: 10.1038/s41598-018-30412-x
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni infection is associated with quantitative and qualitative modifications of the mammalian intestinal microbiota

Abstract: In spite of the extensive contribution of intestinal pathology to the pathophysiology of schistosomiasis, little is known of the impact of schistosome infection on the composition of the gut microbiota of its mammalian host. Here, we characterised the fluctuations in the composition of the gut microbial flora of the small and large intestine, as well as the changes in abundance of individual microbial species, of mice experimentally infected with Schistosoma mansoni with the goal of identifying microbial taxa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
128
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(140 citation statements)
references
References 61 publications
10
128
2
Order By: Relevance
“…In contrast, in mice infected with conventional male and female worms, with egg deposition leading to intestinal egg granulomatous inflammation and a disrupted intestinal gut barrier, the intestinal microbiome had attributes similar to that of DSS-treated mice, reflecting a colitogenic microbiome. A similar dysbiosis as described here in the intestinal microbiota of MF-infected mice after egg laying and the associated intestinal egg granuloma formation were described previously (20). Indeed, there are supporting data showing that an intact intestinal host microbiota is required during S. mansoni infection of mice (21).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, in mice infected with conventional male and female worms, with egg deposition leading to intestinal egg granulomatous inflammation and a disrupted intestinal gut barrier, the intestinal microbiome had attributes similar to that of DSS-treated mice, reflecting a colitogenic microbiome. A similar dysbiosis as described here in the intestinal microbiota of MF-infected mice after egg laying and the associated intestinal egg granuloma formation were described previously (20). Indeed, there are supporting data showing that an intact intestinal host microbiota is required during S. mansoni infection of mice (21).…”
Section: Discussionsupporting
confidence: 89%
“…For instance, in a mouse model of S. japonicum Ova-induced granulomas, a signi cantly higher beta diversity was detected versus controls [23]. Similarly, an overall reduction in alpha and a signi cant increase in beta diversities were found in the gut of S. mansoni infected mice compared to uninfected controls [21]. However, some studies align with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies using not only animal models but also human clinical samples have demonstrated a clear relationship between gut microbiota alterations and Schistosoma spp. infection [20,21,22,23,24,25]. However, no study has explored the relationship between gut microbiota and S. japonicum infectioninduced liver cirrhosis; the potential role of gut microbiota alterations in disease onset and progression is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in our works, an overall reduction in GM alpha diversity in co-infected group was found compared with mono-infected samples, but the community of co-infected group were featured by expanded populations of dominant bacterial community. Among them Epsilonbacteraeota is reassigned as preponderant species in microbial communities as a novel phylum [47,48]. Peer works also showed that mice depleted with Escherichia-Shigella, secondary bile acid-producing bacteria, after antibiotic treatment, were resistant to metabolic improvement [49].…”
Section: Discussionmentioning
confidence: 99%